2019
DOI: 10.3892/mmr.2019.10387
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑30a regulates cell proliferation, migration, invasion and apoptosis in human nasopharyngeal carcinoma via targeted regulation of ZEB2

Abstract: MicroRNA-30a (miR-30a) was previously reported to serve as a tumor suppressor able to inhibit the development and progression of certain types of cancer. A number of previous studies demonstrated that zinc finger E-box binding homeobox 2 (ZEB2) may be regulated by miR-30a in clear cell renal cell carcinoma and breast cancer. However, the function of miR-30a in human nasopharyngeal carcinoma (NPC) remains unclear. The present study aimed to investigate the association between miR-30a and ZEB2 in NPC. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As previous report, the metastasis-associated function of ZEB2 has been demonstrated in multiple tumors, including BC [ 13 ]. Analogously, Chen et al [ 14 ] also found that miR-30a inhibited migration and invasion of nasopharyngeal carcinoma cells by modulating ZEB2.…”
Section: Introductionmentioning
confidence: 77%
“…As previous report, the metastasis-associated function of ZEB2 has been demonstrated in multiple tumors, including BC [ 13 ]. Analogously, Chen et al [ 14 ] also found that miR-30a inhibited migration and invasion of nasopharyngeal carcinoma cells by modulating ZEB2.…”
Section: Introductionmentioning
confidence: 77%
“…In this way, they can act as oncogenic-microRNAs (onco-miRNA) or tumor suppressive-microRNAs. It was shown in different articles that numerous microRNAs—including miR-653 in breast cancer, miR-30a in nasopharyngeal carcinoma, miR-154 in hepatocellular carcinoma by targeting ZEB2—induce apoptosis and cell death [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZEB inhibits the expression of E-cadherin by binding independently to the [CACCT (G)] sequences of the E-cadherin promoter, which results in epithelial-mesenchymal transformation, thus enhancing cell metastasis and invasion 22 . ZEB2 has been shown to enhance the invasion and metastasis of a variety of malignant tumors including colorectal cancer 23 , gastric cancer 24 , breast cancer 25 , bladder cancer 26 , and nasopharyngeal carcinoma 27 . Recent studies have also shown that ZEB2 is highly expressed in ccRCCs and that its expression level is closely related to progression-free and overall survival rate of renal cell carcinoma 28 .…”
Section: Discussionmentioning
confidence: 99%